2016
DOI: 10.1111/pde.13026
|View full text |Cite
|
Sign up to set email alerts
|

Epidermolysis Bullosa with Pyloric Atresia and Significant Urologic Involvement

Abstract: Epidermolysis bullosa (EB) is a rare inherited disease that causes epidermal fragility, blistering, and erosions. EB results from a variety of mutations in proteins of the skin and mucous membranes of the body. Mutations in plectin a protein involved in hemidesmosome integrity and function, are associated with subtypes of EB, including EB with pyloric atresia and EB with muscular dystrophy. We present two cases of EB with significant urologic involvement resulting from mutations in plectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Studies on a larger number of patients with both EB subtypes could provide different data. Also, in this study classification into two subgroups according to subtype of the disease (DDEB and RDEB) was made on the basis of standard diagnostic tests and skin biopsy, as well as according to their rather different clinical features based on which these two forms of EB can be distinguished with high certainty [1][2][3][4][5][6][7]21 . It is important to note that patients with EB in the country were this research was performed are rarely subjected to genetic testing in order to determine what type of inheritance is involved, primarily because of the very high cost of such analyzes and because it is often necessary to conduct such tests abroad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on a larger number of patients with both EB subtypes could provide different data. Also, in this study classification into two subgroups according to subtype of the disease (DDEB and RDEB) was made on the basis of standard diagnostic tests and skin biopsy, as well as according to their rather different clinical features based on which these two forms of EB can be distinguished with high certainty [1][2][3][4][5][6][7]21 . It is important to note that patients with EB in the country were this research was performed are rarely subjected to genetic testing in order to determine what type of inheritance is involved, primarily because of the very high cost of such analyzes and because it is often necessary to conduct such tests abroad.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal and urogenital tract changes, eye changes, and cardiovascular system diseases are also present 6,7 . Chronic loss of blood, iron and nutrients combined with inflammation and damage to the small intestinal mucosa lead to malnutrition, anemia, and retardation in the physical development of these patients 8 .…”
Section: Introductionmentioning
confidence: 99%
“…La epidermólisis ampollosa integra un raro grupo de alteraciones genéticas con fenotipos diversos ( 12 , 13 ) y ocurre en dos de cada 1’000.000 de nacidos vivos ( 2 ). Se caracteriza por fragilidad cutánea con formación de vesículas en la piel derivadas de pequeños traumas, y se categoriza por microscopía electrónica, según la profundidad de la separación de la membrana basal, en tres grupos: simple, de la unión (dermoepidérmica) y distrófica ( 7 ).…”
Section: Discussionunclassified
“…Phenotype-genotype correlations have suggested that EBS-MD is mostly due to genetic variants in the central rod domain of plectin and EBS-PA due to mutations outside this domain (3,8). Urinary tract involvement has only very rarely been reported in patients with either EBS-PA or EBS-MD (3,4). To our knowledge only one case of EBS with both PA and MD, due to compound heterozygous PLEC mutations located in exon 32, has been reported (9).…”
mentioning
confidence: 94%
“…Approximately 8% of patients with EBS are estimated to carry PLEC mutations (2). The PLEC gene encodes the large cytolinker protein plectin (3)(4)(5). Plectin mutations, inherited in an autosomal recessive pattern, result in distinct phenotypes, including EBS with muscular dystrophy (MD), EBS with pyloric atresia (PA) and EBS with skin lesions only (3,6).…”
mentioning
confidence: 99%